Framing fat : competing constructions in contemporary culture - Kwan, Samantha; Graves, Jennifer, 1983- (UPCC book collections on Project MUSE. Global Cultural Studies., 2013)
"According to public health officials, obesity poses significant health risks and has become a modern-day epidemic. A closer look at this so-called epidemic, however, suggests that there are multiple perspectives on the fat body, not all of which view obesity as a health hazard. Alongside public health officials at the Centers for Disease Control and Prevention are advertisers of the fashion-beauty complex, food industry advocates at the Center for Consumer Freedom, and activists at the National Association to Advance Fat Acceptance. Framing Fat takes a bird's-eye view of how these multiple actors construct the fat body by identifying the messages these groups put forth, particularly where issues of beauty, health, choice and responsibility, and social justice are concerned. Samantha Kwan and Jennifer Graves examine how laypersons respond to these conflicting messages and illustrate the gendered, raced, and classed implications within them. In doing so, they shed light on how dominant ideas about body fat have led to the moral indictment of body nonconformists, essentially 'framing' them for their fat bodies."--Publisher's website.